An open-label study examining the effect of pharmacological treatment on mannitol- and exercise-induced airway hyperresponsiveness in asthmatic children and adolescents with exercise-induced bronchoconstriction - Török, Salome Schafroth (BioMed Central, 2014)
BACKGROUND: Mannitol- and exercise bronchial provocation tests are both used to diagnose exercise-induced bronchoconstriction. The study aim was to compare the short-term treatment response to budesonide and montelukast on airway hyperresponsiveness to mannitol challenge test and to exercise challenge test in children and adolescents with exercise-induced bronchoconstriction. METHODS: Patients were recruited from a paediatric asthma rehabilitation clinic located in the Swiss Alps. Individuals with exercise-induced bronchoconstriction and a positive result in the exercise challenge test underwent mannitol challenge test on day 0. All subjects then received a treatment with 400 μg budesonide and bronchodilators as needed for 7 days, after which exercise- and mannitol-challenge tests were repeated (day 7). Montelukast was then added to the previous treatment and both tests were repeated again after 7 days (day 14). RESULTS: Of 26 children and adolescents with exercise-induced bronchoconstriction, 14 had a positive exercise challenge test at baseline and were included in the intervention study. Seven of 14 (50%) also had a positive mannitol challenge test. There was a strong correlation between airway responsiveness to exercise and to mannitol at baseline (r = 0.560, p = 0.037). Treatment with budesonide and montelukast decreased airway hyperresponsiveness to exercise challenge test and to a lesser degree to mannitol challenge test. The fall in forced expiratory volume in one second during exercise challenge test was 21.7% on day 0 compared to 6.7% on day 14 (p = 0.001) and the mannitol challenge test dose response ratio was 0.036%/mg on day 0 compared to 0.013%/mg on day 14 (p = 0.067). CONCLUSION: Short-term treatment with an inhaled corticosteroid and an additional leukotriene receptor antagonist in children and adolescents with exercise-induced bronchoconstriction decreases airway hyperresponsiveness to exercise and to mannitol.